Absolute Configuration of Small Molecules by Co‐Crystallization. Issue 37 (29th June 2020) - Krupp, Felix; Frey, Wolfgang; Richert, Clemens
Abstract: The most reliable method to determine the absolute configuration of chiral molecules is X‐ray crystallography, but small molecules can be difficult to crystallize. We report rapid co‐crystallization of tetraaryladamantanes with small molecules as different as n ‐decane to nicotine to produce crystals for X‐ray analysis and the assignment of absolute configuration when the molecules are chiral. A screen of 52 diverse compounds gave inclusion in co‐crystals for 88 % of all cases and a high‐resolution structure in 77 % of cases. Furthermore, starting from three milligrams of analyte, a combination of NMR spectroscopy and X‐ray crystallography produced a full structure in less than three days using an adamantane crystallization chaperone that encapsulates the analyte at room temperature. Abstract : The absolute configuration of difficult‐to‐crystallize small molecules can be obtained by rapid thermal co‐crystallization with TEO, a tetraaryladamantane octaether, and X‐ray crystallography. As little as 3–5 mg of analyte can produce both NMR and diffraction data within 48 hours.